Making innovative landscapes. Balmori Associates redefining the human-nature relationship for the cities of the future - Javier González-Campaña; Noemie Lafaurie-Debany; Marta Rabazo Martin (Agathón)
In the context of the current scholarly debate on environmental and ecological emergency, the contribution presents the work of landscape architect Diana Balmori and Balmori Associates, which has emerged as one of the most visionary and innovative in combating climate change and creating more liveable cities. The description of some of the work carried out by the Firm helps illustrate the foundational and representative elements that characterise its design work, but more importantly, the strategies to be deployed in order to successfully respond to current critical environmental issues. Diana Balmori’s work is a rare compendium of interventions grounded in scientific research and capable of silently but steadily influencing our current vision of Landscape Architecture, laying solid foundations for a more liveable, sustainable, equitable and accessible urban space and for the creation of ‘operational’ landscapes that help define a new relationship between the 21st-century city and nature.